(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
In order to enable fast medical response in times of pandemics or other humanitarian crises, decentralized manufacturing networks based on additive manufacturing technologies are suitable for the demand-driven production of protective equipment and medical supplies. The use of mobile manufacturing units is intended to increase the resilience of isolated and overwhelmed hospitals in developing countries. In this paper, a digital assistance system for enabling untrained staff to handle the mobile manufacturing unit as well as operate and maintain 3D printers on site will be discussed.